Kerangka Pembelajaran IPA Berbasis Socio-Scientific Issues-Science, Technology, Reading, Engineering, Art, and Mathematics (SSI-STREAM) dalam Memfasilitasi Literasi Sains - Amalia Rahmadani (Universitas Negeri Makassar, 2025)
This study aims to develop a science learning framework based on Socio-Scientific Issues–Science, Technology, Reading, Engineering, Arts, and Mathematics (SSI-STREAM) in order to facilitate students' scientific literacy. The research method used is Qualitative Research Synthesis with four stages, namely determining the topic, searching the literature through a database using the keywords “Socio-scientific Issues”, “Science, Technology, Reading, Engineering, Arts, and Mathematics”, and “Scientific Literacy”, extracting findings, and synthesizing the findings into a learning framework. The results of the study show that SSI is an authentic, controversial, debated issue and directly related to science content, making it relevant for use in science learning. The stages of SSI-based learning that have been synthesized include the presentation of SSI issues, analysis of SSI issues based on science content, the development of arguments in accordance with morals and ethics, and conclusion and evaluation. Meanwhile, the STREAM concept covers six main aspects: Science (understanding natural phenomena); Technology (using devices to obtain information); Reading, which focuses on text comprehension; Engineering (problem-solving skills); Arts (creativity, empathy, and concern); and Mathematics (measurement). Meanwhile, the synthesis of indicators on scientific literacy obtained two aspects, namely the competency aspect and the knowledge aspect. The competency aspect includes the ability to explain scientific issues, identify scientific issues, and design scientific investigations. The knowledge aspect includes content knowledge, procedural knowledge, and epistemic knowledge. Based on these findings, this study produced an SSI-STREAM learning framework that can be used to facilitate students' scientific literacy.